Fungsi Upacara Gawai Dayak dalam Pembelajaran Bahasa Daerah dan Sastra - Sigit Widiyarto; Dadang Sunendar; Sumiyadi Sumiyadi; Iskandar Wassid (Peneliti.net, 2020)
The purpose of this research is to describe the value of the traditional ceremony of the Gawai (rice interest rate) Kapuas Hulu Dayak West Kalimantan tribe. The author is interested in exploring the Gawai ceremony in order to learn about the culture inherited from ancestors and can be used in literary learning. This type of research uses descriptive qualitative methods, namely to obtain information and description of the form, function, and value of speech in the Gawai ceremony based on folklore studies. Sources of research data were taken from field research and were obtained from speakers. Data collection techniques used through observation and interview techniques. Data analysis techniques using data reduction, data presentation, and making conclusions. The results of the study show how learning for students is to overcome these activities, and appreciate activities, by writing, this ritual is an internalization and appreciation, in order to preserve and develop regional culture and literature, by providing information and meaning in depth. The activity of reading and reading the text of prayer and meaning, is expected to determine what is bad, what is evil and good spirit. Beneficial values ​​and sincerity that can be applied to the Jubata (god).